Interstage somatic growth in children with hypoplastic left heart syndrome after initial palliation with the hybrid procedure. (8th April 2016) - Chan, Fiona T. S.; Bellsham-Revell, Hannah R.; Duggan, Hannah; Simpson, John M.; Hulse, Tony; Bell, Aaron J.
Abstract: Introduction: The hybrid procedure is one mode of initial palliation for hypoplastic left heart syndrome. Subsequently, patients proceed with either the "three-stage" pathway – comprehensive second stage followed by Fontan completion – or the "four-stage" pathway – Norwood procedure, hemi-Fontan, or Fontan completion. In this study, we describe somatic growth patterns observed in the hybrid groups and a comparison primary Norwood group. Methods: A retrospective analysis of patients who have undergone hybrid procedure and Fontan completion was performed. Weight-for-age and height-for-age z-scores were recorded at each operation. Results: We identified 13 hybrid patients – eight in the three-stage pathway and five in the four-stage pathway – and 49 Norwood patients. Weight: three stage: weight decreased from hybrid procedure to comprehensive second stage (−0.4±1.3 versus −2.3±1.4, p<0.01) and then increased to Fontan completion (−0.4±1.5 versus −0.6±1.4, p<0.01); four stage: weight decreased from hybrid procedure to Norwood (−2.0±1.4 versus −3.3±0.9, p=0.06), then stabilised to hemi-Fontan. Weight increased from hemi-Fontan to Fontan completion (−2.7±0.6 versus −1.0±0.7, p=0.01); primary Norwood group: weight decreased from Norwood to hemi-Fontan (p<0.001) and then increased to Fontan completion (p<0.001). Height: height declined from hybrid procedure to Fontan completion in the three-stage group. In the four-stage group, height decreased from hybrid to hemi-Fontan, and then increased to Fontan completion. The Norwood group decreased in height from Norwood to hemi-Fontan, followed by an increase to Fontan completion. Conclusion: In this study, we show that patients undergoing the hybrid procedure have poor weight gain before superior cavopulmonary connection, before returning to baseline by Fontan completion. This study identifies key periods to target poor somatic growth, a risk factor of morbidity and worse neurodevelopmental outcomes.